PERANCANGAN SISTEM POMPA AIR SUNGAI YEH HA UNTUK MEMENUHI KEBUTUHAN AIR MASYARAKAT DESA ABABI - Derren, M.; Ariastina, W. G.; Setiawan, I N.; Giriantari, I. A. D.; Sukerayasa, I W.; Satya Kumara, I N. (Program Studi Teknik Elektro UNUD, 2024)
Kayuan Yeh Ha serves as a clean water source located in Ababi Village, Karangasem Regency. The flow from Kayuan Yeh Ha is utilized for both bathing dan consumption by the surrounding residents. Originating from the Yeh Ha spring, Kayuan Yeh Ha is extensively utilized to fulfill the needs of the local community. In order to meet the water requirements of the local populace, a water storage tank with a capacity of 58.74 m3 was initially established to distribute water to 10 households. In the year 2020, a water wheel was employed to power a mechanical pump without electricity to fill the storage tank. After operating for one year, the water wheel experienced shaft damage, necessitating its replacement with a hydraulic ram pump. However, the hydraulic ram pump only utilizes one-fifth of the available water flow, thereby rendering it less effective. Consequently, this research aims to design an electric water pump system powered by a new renewable energy source. The implementation of this electric water pump is expected to enhance the efficiency of filling the storage tank. Based on measurements dan calculations, the micro-hydro power plant system (PLTMH) is estimated to produce a power output of 6kW. Pump selection is determined by electrical power calculations, water discharge, dan pump prices, leading to the adoption of the Pedrollo F50-160B centrifugal pump capable of delivering a water discharge of 56m3/hour at a head of 25 meters. The Pedrollo F50-160 pump utilizes a 3-phase squirrel cage induction motor generating a power output of 5.5kW. Pipe losses dan fittings are also calculated using Pipeflow Expert software, resulting in a water discharge of 31.687 m3/hour. The pump will be operated at maximum capacity for 24 hours, enabling it to deliver a water discharge of 763,620 m3/day, sufficient to meet the clean water needs of 12,277 individuals or 2,455 families. Achieving this water usage target also necessitates piping to households from the storage tank, totaling 35,900 meters in length with an 80mm diameter dan 49,100 meters of 16mm diameter piping. This system is also equipped with a variable frequency drive or inverter device to enhance the efficiency of the electric pump dan reduce starting current surges, simulated for its performance through Simulink software.